Karsinoma Nasofaring Pada Pasien Pria Usia 51 Tahun - Faiq Razaan; Fivien Fedriani (Medula, 2026)
Nasopharyngeal carcinoma is a malignant epithelial tumor arising from the nasopharynx and remains one of the most common head and neck cancers in Indonesia. Its etiology is multifactorial, involving Epstein-Barr virus infection, genetic susceptibility, and environmental exposures such as smoking and consumption of preserved foods. Because early symptoms are often nonspecific, many patients present at an advanced stage. This case report describes the clinical manifestations, risk factors, and diagnostic approach in a 51-year-old man with nasopharyngeal carcinoma and orbital infiltration. The patient presented with a progressively enlarging neck mass for nine months accompanied by hearing loss, tinnitus, epistaxis, diplopia, right-sided facial numbness, nausea, and fatigue. Physical examination revealed cervical lymphadenopathy, right ptosis, anisocoria, multiple cranial nerve deficits, and unilateral hearing impairment. Head computed tomography demonstrated a mass extending to adjacent structures with compression of the optic nerve, while histopathological examination of the nasopharyngeal biopsy revealed keratinizing squamous cell carcinoma, confirming the diagnosis of nasopharyngeal carcinoma with orbital infiltration. The patient had a long history of heavy smoking and frequent consumption of salted fish, both recognized risk factors for this malignancy. Initial management consisted of symptomatic and supportive treatment, followed by referral to a tertiary oncology center for definitive chemoradiotherapy. This case highlights the importance of early recognition of persistent cervical lymphadenopathy and cranial nerve involvement to facilitate timely diagnosis, appropriate staging, and improved clinical outcomes in patients with nasopharyngeal carcinoma.